2011
DOI: 10.1007/s11764-010-0165-3
|View full text |Cite
|
Sign up to set email alerts
|

Towards a personalised approach to aftercare: a review of cancer follow-up in the UK

Abstract: Increasing patient confidence to initiate follow-up specific to their needs is likely to increase the workload of primary care providers, who will need training for this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 30 publications
2
70
1
4
Order By: Relevance
“…There is little evidence of the benefits of using PROMs in follow-up care for cancer survivors due to the paucity of quality studies [21], however early research suggests that alternative methods to traditional hospital-based care such as telephone-based or nurse-led or GP led care are acceptable to patients and do not compromise safety or quality of life [22,23]. This approach can be extended to follow-up care utilising PROMs in redesigned care pathways.…”
Section: Integration Of Proms Into Clinical Practicementioning
confidence: 99%
“…There is little evidence of the benefits of using PROMs in follow-up care for cancer survivors due to the paucity of quality studies [21], however early research suggests that alternative methods to traditional hospital-based care such as telephone-based or nurse-led or GP led care are acceptable to patients and do not compromise safety or quality of life [22,23]. This approach can be extended to follow-up care utilising PROMs in redesigned care pathways.…”
Section: Integration Of Proms Into Clinical Practicementioning
confidence: 99%
“…For prostate cancer, like other cancers, follow-up care after active treatment is important for detection of both disease recurrence and immediate and late occurring side effects of the cancer or its treatment. For prostate cancer, these can include physical problems, such as incontinence or sexual dysfunction, and psychosocial problems, such as depression [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, prostate cancer follow-up care has been within the hospital setting and included regular visits to a specialist clinician for at least several years; indeed, some patients are never discharged from follow-up [3]. With growing numbers of survivors, this model of care has been argued to be economically unsustainable [4], and there is interest in developing alternative approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The ncsi is convinced that few recurrences are found that way and that that method is ineffective and inefficient for follow-up care 53 . Multiple evaluations conducted by the ncsi have shown that their broader, personalized approach can lead to improvements in several outcomes, including patient satisfaction [54][55][56] , patient confidence in self-managing their own health 56 , cost effectiveness 42,54 , and reduced demand for acute care and outpatient resources 54,57,58 .…”
Section: Financial Concerns 6 (38)mentioning
confidence: 99%